Building Adolescent Assertiveness Awareness Through Individual Counseling Services: A Psychoeducational Approach - Danni, Ulfa; Ahmad, Fitri (PPG IKIP Siliwangi, 2025)
Adolescents often face difficulties in expressing thoughts and feelings appropriately, which indicates low assertiveness awareness. Lack of assertiveness can lead to social pressure, interpersonal conflict, and decreased psychological well-being. This study aims to examine how individual counseling services with a psychoeducational approach can build assertiveness awareness in adolescents. This study uses a literature review design by examining scientific sources from relevant national and international journals in the past five years. The search procedure was carried out through databases such as Google Scholar, ResearchGate, and ScienceDirect using the keywords